COMMUNICATIVE COMPETENCE OF MIDWIVES EXPRESSED IN COMMUNICATION WITH COLLEAGUES - Zdravka Atanasova; Kremena Miteva (Peytchinski Publishing, 2020)
Background: Effective service to patients by medical teams largely depends on the optimal course of interactions between the members, on their communicative competence, their ability to solve problems, disputes and conflicts. Aim: This scientific report aims to explore and analyze the competence of modern midwives /practising their profession and trainees in the speciality/ to conduct a conversation with colleagues in medical institutions for obstetric care. Material and methods: Questionnaire method, monitoring, mathematics - statistical methods. The volume of the representative sample - 241 respondents. Results: Midwives /practising the profession and the trainees in the speciality/ adhere to different patterns of behaviour when communicating with colleagues. Conclusion: The most effective communication with colleagues is held by midwives with degrees "Bachelor" and "Master" in HCM. For most of them, it could be said that they have the "ability to be assertive." They clearly express their needs and desires; actively listen to his interlocutors; their behaviour is fair, direct, non-destructive, suitable for the environment and culture of the medical team. That interaction is a positive way to deal with stress in the profession of the midwife.